Insights for enhancing monitoring, evaluation and learning: A case study from the Enhancing Climate-Change Resilience in East Africa (ECREA) Project - Ngige, Chris Mwangi; Kagabo, Desire; Mvuyibwami, Patrick; Eitzinger, Anton (2025)
This insight note presents the 5Q Approach, an innovative monitoring, evaluation, and learning (MEL) method applied in the Enhancing Climate-Change Resilience in East Africa (ECREA) project. It leverages low-cost mobile technology (IVR/SMS) and five standardized questions to collect real-time, scalable data from remote farming communities on the use of bundled Agroclimate Advisories. The approach overcomes literacy barriers through multilingual voice surveys and provides immediate, actionable insights via dynamic dashboards. This enables inclusive, data-driven decision-making and adaptive project management, strengthening climate resilience by improving the reach and use of weather and climate information services (WCIS) for bean farmers in East Africa.